Layer-by-layer pH-sensitive nanoparticles for drug delivery and controlled release with improved therapeutic efficacy in vivo - Men, Wanfu (Drug Deliv, 2020)
In this work, a pH-sensitive liposome–polymer nanoparticle (NP) composed of lipid, hyaluronic acid (HA) and poly(β-amino ester) (PBAE) was prepared using layer-by-layer (LbL) method for doxorubicin (DOX) targeted delivery and controlled release to enhance the cancer treatment efficacy. The NP with pH-sensitivity and targeting effect was successfully prepared by validation of charge reversal and increase of hydrodynamic diameter after each deposition of functional layer. We further showed the DOX-loaded NP had higher drug loading capacity, suitable particle size, spherical morphology, good uniformity, and high serum stability for drug delivery. We confirmed that the drug release profile was triggered by low pH with sustained release manner in vitro. Confocal microscopy research demonstrated that the NP was able to effectively target and deliver DOX into human non-small cell lung carcinoma (A549) cells in comparison to free DOX. Moreover, the blank NP showed negligible cytotoxicity, and the DOX-loaded NP could efficiently induce the apoptosis of A549 cells as well as free DOX. Notably, in vivo experiment results showed that the DOX-loaded NPs effectively inhibited the growth of tumor, enhanced the survival of tumor-bearing mice and improved the therapeutic efficacy with reduced side-effect comparing with free drug. Therefore, the NP could be a potential intelligent anticancer drug delivery carrier for cancer chemotherapy, and the LbL method might be a useful strategy to prepare multi-functional platform for drug delivery.